2005
DOI: 10.1111/j.1601-0825.2005.01101.x
|View full text |Cite
|
Sign up to set email alerts
|

Subjective patients’ opinion and evaluation of halitosis using halimeter and organoleptic scores

Abstract: A statistically significant correlation was found between clinical organoleptic diagnosis of halitosis and VSC level by halimeter. Subjective patients' opinion correlated well with objective evaluation of halitosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
2
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 6 publications
2
30
2
7
Order By: Relevance
“…Nevertheless, many studies have shown a positive correlation between an individual's self-perception about his oral health and his real condition, considering that self-perception is a predictor of oral status and may even be used as a therapeutic planning tool. 31,32 Moreover, from a clinical perspective, individual-centered outcomes have been more frequently used in the dental literature, and self-reported halitosis fits this scenario well. The strengths of this study may also include the sample size and the high response rate, which allowed applying multivariable analytical models that control confounding factors.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, many studies have shown a positive correlation between an individual's self-perception about his oral health and his real condition, considering that self-perception is a predictor of oral status and may even be used as a therapeutic planning tool. 31,32 Moreover, from a clinical perspective, individual-centered outcomes have been more frequently used in the dental literature, and self-reported halitosis fits this scenario well. The strengths of this study may also include the sample size and the high response rate, which allowed applying multivariable analytical models that control confounding factors.…”
Section: Discussionmentioning
confidence: 96%
“…This has been argued in the literature where one study showed a weak correlation between objective and self-reported halitosis [31]. In contrast, Iwanicka-Grzegorek et al ., [32] reported an agreement between self-perceived and objective evaluation of halitosis. Objective methods for measuring halitosis are organoleptic measurement, gas chromatography, and sulfide monitoring.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies in clinical populations suggest poor agreement, 1,4 leading to the concept that there is a "bad breath paradox-people suffering from breath odor being completely unaware of their problem, whereas others are convinced that they have a problem where nothing was found" 7 Conversely, self-assessment of halitosis appears to be both more reliable and more valid in a general population than in highly selected patients. 4,5,14 A recent study 15 suggested that self-estimated halitosis is a fair to good predictor of the presence of objective halitosis, which was considered present if the average level of volatile sulfur compounds was ≥125 ppb and the organoleptic measurement using a 0-5-point scale was ≥2 (sensitivity= 89.0%; specificity=61.4%). Moreover, "objective measurement [sulphide monitoring or gas chromatography] of breath components is rarely used in routine clinical practice, as it is expensive and time consuming."…”
Section: Discussionmentioning
confidence: 99%